Economic Category of 'Value' in Criminal Law and Forensic Science - S. N. Khaziev (Теория и практика судебной экспертизы)
The main provisions of Criminal Law relating to the economic category of ‘value’ are discussed in the article. Text analysis of the Criminal Code of the Russian Federation indicates the need for a uniform understanding of this category, regardless of the criminal law. During the investigation and trial of many types of crimes appraisement is signifcant and needs a deeper comprehension. While appointment, production and evaluation of forensic examinations, the resolution of which raises the question of valuation, inevitable complications arise due to the intricacy of determining the content of the specialized knowledge necessary for their implementation. The main provisions of Criminal Law relating to the economic category of ‘value’ as well as the interpretations of the Supreme Court of the Russian Federation concerning value determination in the Criminal Law are discussed in the article. The inadmissibility of forensic appraisal examinations appointment and conduct is justifed, since the goals and norms of the legislation on appraisal and appraisal activities do not always correspond to the tasks and methods of forensic expert valuation of goods, services, cultural values. The necessity of development of new and improvement of existing forensic expert valuation methods in the framework of such examinations as forensic product examination, forensic economics, construction forensic etc. is presented.